Isolation and Identification of Bacteria from the Workers of Live Bird Markets at Mymensingh, Bangladesh - Sarker, S; Talukder, S; Chowdhury, EH; Das, PM (Journal of Bio-Science, 2011)
Context: Identification of bacteria from the workers of live bird markets is important factor for zoonotic aspects and for implementing appropriate control strategies. Objectives: To determine the occurrence of bacteria especially Salmonella sp. and Escherichia coli from the workers of live bird markets. Materials and Methods: A total of 40 samples were collected from hand washes (n=20) and nasal swabs (n=20) of the associated workers in urban and suburban live bird markets. Bacteria were isolated in different media, and identification was performed based on the staining, cultural and some biochemical tests. For Salmonella sp., DNA was extracted using a DNA isolation kit and rfbs gene was amplified by using commercial PCR kit. Results: The bacteria such as Salmonella sp. and E. coli were detected in the samples by several microbial tests. The prevalence of Salmonella sp. was 40% and 30%, and E. coli was 70% and 40% in the hand washes and nasal swabs respectively of the workers of urban and periurban live bird markets. Conclusion: The results obtained in this study suggest that the appropriate precautions should be taken during and subsequent to the handling of live birds to minimize the risk of zoonotic diseases. Key words: Salmonella; Escherichia coli; live bird markets; isolation and identification DOI: 10.3329/jbs.v17i0.7121 J. bio-sci. 17: 135-138, 2009